1991
DOI: 10.1577/1548-8667(1991)003<0048:hetwct>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hatchery Efficacy Trials with Chloramine-T for Control of Bacterial Gill Disease

Abstract: Three hatchery trials were carried out to determine the efficacy of chloramine-T for the control of bacterial gill disease in rainbow trout Oncorhynchus mykiss, ranging in weight from 2.5 to 54 g. In each trial, we used a single flow-through treatment of 8.5 mg chloramine-T/L. The single treatment provided effective control in all three trials; however, results were best when treatment was begun in the early stages of an outbreak. A second or third treatment may be required if an outbreak is in an advanced sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 1 publication
0
33
0
Order By: Relevance
“…Chloramine-T is used as a bactericide at concentrations ranging from 9-12 ppm for one-hour static bath treatments either singly, or in a series of three treatments given on alternate days (Bills et al 1988;Bullock et al 1991). Single static bath and recycle bath treatments with 9 ppm of chloramine-T (N-chloro-p-toluene sulfonamide sodium salt, Sigma Chemical Co. 1 , St. Louis, MO, USA) were conducted first, and then a multiple static bath treatment consisting of three treatments at 12 ppm was performed on alternate days.…”
Section: Chemotherapeutant Treatmentsmentioning
confidence: 99%
“…Chloramine-T is used as a bactericide at concentrations ranging from 9-12 ppm for one-hour static bath treatments either singly, or in a series of three treatments given on alternate days (Bills et al 1988;Bullock et al 1991). Single static bath and recycle bath treatments with 9 ppm of chloramine-T (N-chloro-p-toluene sulfonamide sodium salt, Sigma Chemical Co. 1 , St. Louis, MO, USA) were conducted first, and then a multiple static bath treatment consisting of three treatments at 12 ppm was performed on alternate days.…”
Section: Chemotherapeutant Treatmentsmentioning
confidence: 99%
“…It was shown that for exposures of less than 3 h the median lethal concentration (LC5,) was more than the 5-10 mg/L recommended for the treatment of bacterial gill disease (From 1980;Speare and Ferguson 1989a;Bullock et al 1991). Toxicity increased in soft water and at lower pH but was reduced with increased organic loading; a higher temperature also increased chloramine-T toxicity (Bills et al 1988a(Bills et al , 1988b.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined the effects of intermittent sublethal exposure of chlorine on salmonids (Heath 1977;Seegert and Brooks 1978;Zeitoun 1978, Seegert et al 1979Booth et al 1981;Brooks and Bartos 1984). These previous studies used concentrations of total residual chlorine greater than those reported as a result of the use of chloramine-T for the control of bacterial gill disease (Bullock et al 1991). In addition, the studies that specifically examined the toxicity of chlorine under various conditions Heath 1977;Seegert and Brooks 1978;Zeitoun 1978;Seegert et al 1979;Booth et al 1981, Brooks andBartos 1984) used more frequent exposure of fish than the chloramine-T treatment regimes used in the aquaculture industry (typically 1 h of exposure per day for up to 3 consecutive days).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the two compounds are used in Italy for tool/tank disinfection in aquaculture, and in other countries also for treatment of fish bacteria, fungi and parasites (Bullock et al 1991, Harris et al 2005, Sudová et al 2010, Straus et al 2012a. Chloramine-T is less affected by organic matter than other chloride compounds; it becomes more toxic in acidic and warm water and in soft water (Bills et al 1988).…”
Section: Discussionmentioning
confidence: 99%